2013
DOI: 10.1523/jneurosci.5206-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Constitutive Endocytosis of Acid-Sensing Ion Channel 1a and Its Protective Function in Acidosis-Induced Neuronal Death

Abstract: Acid-sensing ion channels (ASICs) are proton-gated cation channels widely expressed in the peripheral and CNSs, which critically contribute to a variety of pathophysiological conditions that involve tissue acidosis, such as ischemic stroke and epileptic seizures. However, the trafficking mechanisms of ASICs and the related proteins remain largely unknown. Here, we demonstrate that ASIC1a, the main ASIC subunit in the brain, undergoes constitutive endocytosis in a clathrin- and dynamin-dependent manner in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 58 publications
(88 reference statements)
2
53
1
Order By: Relevance
“…Here, we performed a thorough examination of ASIC1a C-terminal tail and revealed several distinct motifs regulating ASIC1a surface expression and channel properties. Of note, the RRGK motif overlaps with a recently reported LCRRG motif (Zeng et al, 2013, see below for more discussion). These data provide a foundation for future studies of the molecular mechanisms that regulate ASIC1a trafficking and function.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Here, we performed a thorough examination of ASIC1a C-terminal tail and revealed several distinct motifs regulating ASIC1a surface expression and channel properties. Of note, the RRGK motif overlaps with a recently reported LCRRG motif (Zeng et al, 2013, see below for more discussion). These data provide a foundation for future studies of the molecular mechanisms that regulate ASIC1a trafficking and function.…”
Section: Discussionmentioning
confidence: 59%
“…In a recent study, an LCRRG motif, which overlaps with the RRGK motif reported here, is required for the interaction between ASIC1a and AP2, which induces endocytosis of ASIC1a (Zeng et al, 2013). However, the authors also commented that they were unable to assess the endocytosis of the LCRRG mutants using surface biotinylation analysis, because their unpublished data suggest that the same mutants also abolished ASIC1a forward trafficking.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Building on these observations, a recent paper observed that constitutive endocytosis of ASIC1A in a clathrin- and dynamin-dependent manner protected cells against acid-induced cell death 77 . Potential roles of the other ASICs, particularly ASIC2B, have been uncertain, as ASIC2B homomers do not form pH-sensitive channels 7,27 .…”
Section: Asics Neurotoxicity and Neurological Diseasesmentioning
confidence: 92%
“…An acid-sensing ion channel, ASIC1a, is involved in the Ca 2+ influx-inhibiting this channel may be neuro-protective. 154 In addition to the Ca 2+ influx, failure of Ca 2+ efflux contributes to the Ca 2+ accumulation. Prostaglandin E2 EP1 receptors have been implicated in the failure of the Na + /Ca 2+ exchanger during ischemia.…”
Section: Existing Stroke Therapiesmentioning
confidence: 99%